2018
DOI: 10.1111/jems.12284
|View full text |Cite
|
Sign up to set email alerts
|

Wholesale price discrimination: Innovation incentives and upstream competition

Abstract: In intermediate good markets where there are alternative supply sources, wholesale price discrimination may enhance innovation incentives downstream. We consider a vertical chain where a dominant firm and a competitive fringe supply imperfect substitutes to duopoly retailers which carry both varieties. We show that a ban on price discrimination by the dominant supplier makes uniform pricing credible and reduces retailers’ incentives to decrease the cost of acquiring the competitively supplied variety, leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Our analysis also closely relates to the literature on input price discrimination with cost-reducing R&D (e.g., Akgün & Chioveanu, 2019;Herweg & Müller, 2014;Inderst & Valletti, 2009;Pinopoulos, 2020) in the sense that we consider a dynamic model. DeGraba (1990) shows input price discrimination weakens the investment incentive for a firm due to the higher wholesale price charged to efficient firms.…”
Section: Introductionmentioning
confidence: 91%
“…Our analysis also closely relates to the literature on input price discrimination with cost-reducing R&D (e.g., Akgün & Chioveanu, 2019;Herweg & Müller, 2014;Inderst & Valletti, 2009;Pinopoulos, 2020) in the sense that we consider a dynamic model. DeGraba (1990) shows input price discrimination weakens the investment incentive for a firm due to the higher wholesale price charged to efficient firms.…”
Section: Introductionmentioning
confidence: 91%
“…In addition to them, Deng et al (2019), Gozman, Liebenau, and Mangan (2018) and Nuruzzaman, Singh, and Pattnaik (2018) focused on this issue and reached the conclusion that the products and services of competitors are shaped by the company's decision to develop innovative products. On the other side, Akgün and Chioveanu (2019), Marshall and Parra (2019) and Negassi et al (2019) identified that although a company develops an innovative product, if it fails to meet its needs in comparison with its competitors' products, this will have a negative impact on the company. The importance of market analysis in generating innovative product was also underlined by different researchers (Liu et al, 2018; Weimann, 2019; Xia & Liu, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study is entirely analytical and uses game-theoretic models (Hamamura, 2022; Lu et al , 2022; Xie et al , 2022; Zaheri et al , 2021) like Stackelberg game (Chen et al , 2017; Lee et al , 2021; Li et al , 2018; Tang et al , 2021; Zhang and He, 2016; Zhao et al , 2020) and horizontal Nash game (Farham-Nia and Ghaffari-Hadigheh, 2021; Li et al , 2018; Zhang and Hezarkhani, 2021; Zhao et al , 2020) for the analysis. This is mainly because wholesale prices are not widely collected and analysed like retail prices (De Giovanni, 2018; Rofin and Mahanty, 2020, 2021; Akgün and Chioveanu, 2019; Marshall, 2020). Thus, rather than empirical methods, analytical methods are convenient and reliable for analysing wholesale price.…”
Section: Introductionmentioning
confidence: 99%
“…Analysing the wholesale price charged by the manufacturer is essential as its trickledown effect significantly impacts the profit margin of all the downstream channel partners and the consumer surplus of the customers (De Giovanni, 2018; Rofin and Mahanty, 2020, 2021). Two schemes are available for wholesale pricing EWP, which translates to selling at the same wholesale price to all the downstream channel partners and DWP, which means selling products to different manufacturers at different wholesale prices (Akgün and Chioveanu, 2019; Marshall, 2020). But many countries consider that the DWP is against fair competition and prohibits it by law (Rofin and Mahanty, 2020, 2021).…”
Section: Introductionmentioning
confidence: 99%